Revision of Beardius Reiss et Sublette, 1985 (Diptera: Chironomidae), with the description of twenty new species - Pinho, Luiz Carlos; Mendes, Humberto Fonseca; Andersen, Trond (Zootaxa, 2013)
The genus Beardius Reiss et Sublette, 1985 is revised and twenty new species, Beardius abbadi sp. n., B. arawak sp. n., B. bizzoi sp. n., B. bucephalus sp. n., B. curticaudatus sp. n., B. dioi sp. n., B. hirtidorsum sp. n., B. krenak sp. n., B. kumadueni sp. n., B. longicaudatus sp. n., B. mileneae sp. n., B. nebularius sp. n., B. neusae sp. n., B. novoairensis sp. n., B. phoenix sp. n., B. sapiranga sp. n., B. tupinamba sp. n., B. vanessae sp. n., and B. yperoig sp. n. from Brazil and Beardius chapala sp. n. from Mexico are described and figured. Further, the female, pupa and larva of B. urupeatan Pinho, Mendes et Andersen and the female and larva of B. cristhinae Trivinho-Strixino et Siqueira are described, and new records of Brazilian species are provided. Emended diagnoses for all stages and sexes are given. The phylogeny of the genus is outlined and seven tentative species groups, the parcus group, the truncatus group, the tupinamba group, the triangulatus group, the bucephalus group, the xylophilus group, and the roquei group, are proposed. Keys to males, females, pupae and larvae are provided.